Effect of Particle Shape on Monotonic Liquefaction: Natural and Crushed Sand - Keramatikerman, M.; Chegenizadeh, Amin (Springer, 2017)
This study investigates the effect of particle shape on monotonic liquefaction of the soil by performing a series of static triaxial compression tests. The tests conducted on three types of natural sand (NS), crushed sand (CS), and mixed sand (MS) (i.e., 50% natural sand +50% crushed sand by dry weight of the soil) with different particle shape descriptors consist of roundness (R), sphericity (S), and regularity (ρ). The shearing responses showed that the CS and MS specimens showed a dilative response whereas the natural sand had a strain-softening contractive behaviour. Also, the interpreted results based on a framework of the critical state of the soil mechanic (CSSM) showed that in e-p′ plane, the specimen with a higher amount of crushed particles have a greater strength due to a higher packing characteristics. The investigations on critical state locus on q-p′ plane showed that by increasing the roundness, sphericity and regularity of the specimens the critical friction angle (ϕcs) decreased. Also, studies on flow liquefaction in undrained instability state (UIS) showed that by increasing the particle shape descriptor values, the specimens are more prone to be liquefied.